Acute aerobic exercise does not cause DNA damage in trained individuals after a running session - Tagliari, Nelson João (2019)
Performing long-duration exercise may increase oxygen consumption, which may result in redox imbalance inducing a frame of oxidative stress. The aim of the present study was to analyze the effects of EROS after a training session on the DNA of human lymphocytes and biochemical parameters (TBARS, triglycerides, proteins, glucose, albumin, and urea). A cross-sectional, descriptive and analytical study of 18 Caucasian individuals, males, between 18 and 35 years of age, underwent a continuous aerobic training session (60-minute run with intensity comprised between 70% and 75% of the maximum heart rate. The participants had a mean age of 21.78 ± 3.82 years; body mass 72.04 ± 6.35 kg; Height 1.79 ± 0.05 m, BMI of 22.37 kg/cm2 ± 1.70, fat mass 8.43 ± 3.97 %. Results showed a statistically significant increase in total protein, glucose and triglyceride levels post-exercise, while albumin decreased significantly post-exercise, whereas other biochemical parameters did not present significant change. DNA damage analysis showed no significant effects. We conclude that aerobic training in the conditions herein did not induce damage due to oxidative stress in the studied structures, probably because the individuals were well-trained and previously adapted to the conditions of exercise.